There are two ways to evaluate the square root of 864: using a calculator, and simplifying the root.
The first method is simplifying the root. While this doesn't give you an exact value, it reduces the number inside the root.
Find the prime factorization of 864:
[tex]\sqrt{864} = \sqrt{2 \cdot 2 \cdot 2 \cdot 2 \cdot 2 \cdot 3 \cdot 3 \cdot 3}[/tex]
Take any number that is repeated twice in the square root, and move it outside of the root:
[tex]\sqrt{864} = \sqrt{(2 \cdot 2) \cdot (2 \cdot 2) \cdot 2 \cdot (3 \cdot 3) \cdot 3}[/tex]
[tex]\sqrt{2 \cdot 2} = \sqrt{4} = 2[/tex]
[tex]\sqrt{3 \cdot 3} = \sqrt{9} = 3[/tex]
[tex]\sqrt{(2 \cdot 2) \cdot (2 \cdot 2) \cdot 2 \cdot (3 \cdot 3) \cdot 3} = \sqrt{(4) \cdot (4) \cdot 2 \cdot (9) \cdot 3}[/tex]
[tex]\sqrt{(4) \cdot (4) \cdot 2 \cdot (9) \cdot 3} = (2 \cdot 2 \cdot 3) \sqrt{2 \cdot 3} = \boxed{12 \sqrt{6}}[/tex]
The simplified form of √864 will be 12√6.
The second method is evaluating the root. Using a calculator, we can find the exact value of √864.
Plugged into a calculator and rounded to the nearest hundredths value, √864 is equal to 29.39. Because square roots can be negative or positive when evaluated, this means that √864 is equal to ±29.39.
What number divided by 7 equals 7
7 divided by 7 equals 1. So, 7 divided by 1 equals 7.
Hope this helps.
Answer:
49
Step-by-step explanation:
7 squared is 49. 49 divided by 7 = 7
You can fly from Seattle to Boise for $137.50, from Boise to whichita for $92.50 and from whichita to Austin for $162.50, use mental math to find the total cost of the flight from Seattle to austin
What I do is to add up the hundreds and tens in my mind first:
130 + 90 + 160 = 380
and then add the small change:
7.50 + 2.50 + 2.50 = 12.50
and add it back to the first amount
392.50
Its $392.50
All you have to do is add $137.50 + $92.50 + $162.50 = $392.50
Hope the answer helps!
What is the value of X?
X=2.25
X=11.25
X=13
X=22
Answer: The correct option is (D) 22.
Step-by-step explanation: We are given to find the value of x from the given figure.
From the figure, we see that a triangle is shown where the measure of an external angle is (6x + 1)° and the measures of the two remote interior angles are 79° and (2x + 10)°.
Since the sum of the measures of two remote interior angles of a triangle is equal to the measure of the external angle, so we get
[tex]79^circ+(2x+10)^\circ=(6x+1)^\circ\\\\\Rightarrow 79+2x+10=6x+1\\\\\Rightarrow 6x-2x=88\\\\\Rightarrow 4x=88\\\\\Rightarrow x=\dfrac{88}{4}\\\\\Rightarrow x=22.[/tex]
Thus, the required value of x is 22.
Option (D) is CORRECT.
Conditional Probability
Answer question please
You can just write anything really
Statement: If David likes to do math then he is a good student.
Hypothesis: David likes to do math
Conclusion: He is a good student.
It's basically a if then statement
im thinking of a number. My number is 5 more then one-half my number. Create an equation based on this situation to find my number.
The equation which represent the number you are thinking x = (1/2)x + 5 your number is 10.
Let's represent the number you are thinking of as "x."
According to the given information, your number is 5 more than one-half of your number. Mathematically, this can be written as:
x = (1/2)x + 5
The equation x = (1/2)x + 5 represents the situation where your number is 5 more than one-half of your number. To find the value of your number (x), you can solve this equation:
Subtract (1/2)x from both sides to isolate x:
x - (1/2)x = (1/2)x + 5 - (1/2)x
(1/2)x = 5
Now, multiply both sides by 2 to get rid of the fraction:
2 * (1/2)x = 2 * 5
x = 10
So, your number is 10.
To know more about equation click here :
https://brainly.com/question/12622770
#SPJ2
Solve math problem 15xy-30y
How much more Ted saved
He saves $20 i did this and i got the right answer. hope this helps mark me as brainliest
what is the mean of 33, 31, 36, 30, 35
27 issssssssssss the eeeeee mean
Rewrite one of the two equations above in the form ax+by=c,where a,b,c are constants,so that the sum of the new equations and the unchanged equations from the original system results in an equation in one variable
To rewrite one equation like x = 4 - y into ax + by = c form, we adjusted it to x + y = 4. Then, we combined it with the unchanged equation y = 2x + 3 by substituting 'y' in the first equation with 'y' from the second, leading to 3x + 3 = 4, a one-variable equation.
Explanation:To rewrite one of the two equations into the form ax + by = c, it's essential to start by having an equation that resembles y = a + bx (which is the same as y = mx + b, the conventional form for a linear equation) and the other in any format initially. Let's assume these equations as the existing ones: y = 2x + 3 and x = 4 - y.
Step 1: Transform the equation x = 4 - y into the form ax + by = c.
Firstly, shift y to the left side of equation by adding 'y' to both sides:
x + y = 4,
That's it! We now have the equation in the required ax + by = c format, where a = 1, b = 1 and c = 4.
Step 2: Add this new equation to the unchanged equation.
x + y = 4 (New one after rearranging)
y = 2x + 3 (Unchanged equation)
By substituting y from the second equation into the first, it will result in an equation in one variable:
x + (2x + 3) = 4,
After simplifying the equation, we get
3x + 3 = 4,
That is the result as an equation in one variable.
Learn more about Linear Equations here:https://brainly.com/question/32634451
#SPJ3
A recipe needs 4 cups of milk and 6 cups of grated cheese. what is the ratio of the number of cups of grated cheese in the recipe? A. 2:3 B. 2:5 C. 6:4 D. 4:10
Which inequality is true?
A. |5| < |–3|
B. |2| < |–4|
C. |–5| < |–3|
D. |–4| < |–2|
need help ASAP
8-x<5 solve the inequality and graph the solution
8 - x < 5 |-8
-x < -3 |change the signs
x > 3
you ran 6 miles in 2 hours on friday. on saturday, you run 18 miles in 6 hours. your rate of change is 3 miles an hour true or false. Need it answered ASAP !!!
6/2 =3
18/3 = 3
(18-6)/((6-2)= 12/4 =3
True
6/2=3
18/6=3
The answer is True
Solve: x2 − x − 6 x2 = x − 6 2x + 2x + 12 x After multiplying each side of the equation by the LCD and simplifying, the resulting equation is
Answer:
C) 3x^2 + 20x + 12 = 0
Step-by-step explanation: Because it is the right answer
What are the solutions to the equation?
A. x = -6 and x = -2/3
Step-by-step explanation:
this was a second part to the question for me so i decided to give u guys it as well, incase u come across it
Unscramble all the words worth a lot of points please help!!!
1. rational number
2. percent
3. least common denominator
4. proportion
5. percent proportion
I am positive that these numbers are correct.
1 is rational number
2 is percent
3 is least common denominator
4 is proportion
5 is percent proportion
In an arithmetic sequence, find a6 when a1 = 13 and d = 4
[tex]a_{6}[/tex] = 33
the n th term of an arithmetic sequence is
[tex]a_{n}[/tex] = [tex]a_{1}[/tex] + (n - 1 )d, hence
[tex]a_{6}[/tex] = 13 + (5 × 4 ) = 13 + 20 = 33
The sixth term (a₆) is 33 in the arithmetic sequence.
What are Arithmetic operations?Arithmetic operations can also be specified by subtracting, dividing, and multiplying built-in functions. The operator that performs the arithmetic operation is called the arithmetic operator.
What is an arithmetic sequence?An arithmetic sequence is defined as an arrangement of numbers that is in a particular order.
The formula to find the general term of an arithmetic sequence is,
aₙ = a₁ + (n-1)d
In arithmetic, sequence d represents the common difference.
Where aₙ is the nth term of the sequence and a₁ is the first term
We have been given that a₁ = 13 and d = 4 in an arithmetic sequence,
Substitute the values in the formula,
⇒ a₆ = 13 + (5 × 4)
⇒ a₆ = 13 + 20
⇒ a₆ = 33
Therefore, the sixth term is 33 in the arithmetic sequence.
Learn more about the arithmetic sequence here:
brainly.com/question/21961097
#SPJ2
What is the solution set of the equation? x^2-14x=14
x^2 - 14x = 14
x^2 - 14x + 49 = 63
(x - 7)^2 = 63
x - 7 = √63
x = 7 ± √63 is the solution set to the provided equation.
What is the remainder when (x4 + 36) is divided by (x2 – 8)? 36 64 100 117
Answer:
c 100
Step-by-step explanation:
Using the long divison method, the remainder when x⁴ + 36 is divided by x² - 8 is 100
Dividend = x⁴ + 36Divisor = x² - 8_____x²+8
___________
x² - 8 | x⁴ + 36
____ | x⁴ - 8x²
-________8x² + 36
-________8x² - 64
___________100
The remainder is calculated as (36 - (-64)) = (36 + 64) = 100
Therefore, the remainder is 100
Learn more : https://brainly.com/question/18109354
Solve
6x−10(x+12)=−4x−24
Show your work.
6x - 10(x + 12) = -4x - 24
Distributive property.
6x - 10x - 120 = -4x - 24
Add 10x to both sides.
6x - 120 = 6x - 24
Cancel like terms.
Add 24 to both sides.
-96 ≠ 0.
This equation is incorrect, as -96 will never be equal to 0.
What is the best estimate for 3 + (-14.9)(-2.3)?
36
31
48
33
A is false
Answer:
33
Step-by-step explanation:
3(5p-3)=5(p-1) what does p equal
The solution of expression is,
p = 2/5
We have to given that,
An expression to solve,
3 (5p - 3) = 5 (p - 1)
Now, We can simplify as,
3 (5p - 3) = 5 (p - 1)
Apply distributive property, we get;
15p - 9 = 5p - 5
15p - 5p = 9 - 5
10p = 4
p = 4/10
p = 2/5
Therefore, The solution of expression is,
p = 2/5
Learn more about the mathematical expression visit:
brainly.com/question/1859113
#SPJ6
What is 64 ounces in 8 cups
128 ounces and 16 cups
64÷8=8
64 1/2 gallon
8 cups
Convert 0.05 into a fraction
the answer is 5/100 because its in the hundreths place but it simplifies down to 1/20
thank you for your time and please mark brainliest
9x+4y= -5 how do I write this as a sum
one number is 6 less than 3 times another number and their sum is 62.find the numbers
y = 6 - 3x
x + y = 62
Since we already know the value of y, we can use substitution to find the value of x.
x + 6 - 3x = 62
Subtract 6 from both sides.
x - 3x = 56
Combine like terms.
-2x = 56
Divide both sides by -2
x = -28
Now that we know the value of x, we can solve for the value of y.
x + y = 62
-28 + y = 62
Add 28 to both sides
y = 90
The value of y is 90, and the value of x is -28 (this is your answer)
To make sure that these values are correct, we can plug them into the original equations.
y = 6 - 3x
x + y = 62
90 = 6 - 3(-28)
90 = 90 √ this is correct
-28 + 90 = 62
62 = 62 √ this is also correct
Final answer:
Using a system of linear equations, we find that the two numbers in question are 45 and 17.
Explanation:
Let's call the first number x and the second number y. According to the problem, one number (x) is 6 less than 3 times another number (y). So we can write this as an equation: x = 3y - 6.
The problem also states that their sum is 62. This gives us a second equation: x + y = 62.
Now, we have two equations:
x = 3y - 6 (Equation 1)
x + y = 62 (Equation 2)
To find the values of x and y, we can substitute the expression for x from Equation 1 into Equation 2, giving us:
(3y - 6) + y = 62
Simplifying, we have:
4y - 6 = 62
Adding 6 to both sides:
4y = 68
Dividing by 4:
y = 17
Now that we have the value for y, we can substitute it back into Equation 1 to find x:
x = 3(17) - 6
x = 51 - 6
x = 45
Therefore, the two numbers are 45 and 17.
simplify (x -3)(x + 7) using the table method, and identify the resulting
Answer:
The simplified form of given expression is [tex]x^2+4x-21[/tex].
Step-by-step explanation:
The given expression is
[tex](x-3)(x+7)[/tex]
Here, we have to factors (x-3) and (x+7).
Factor (x-3) has two terms x and -3. Write these terms in first row.
Factor (x+7) has two terms x and 7. Write these terms in first column.
Now, find the elements of the table by multiplying corresponding rows and columns.
The elements of the table are x², -3x, 7x, -21.
Now, add all these elements.
[tex]x^2-3x+7x-21=x^2+4x-21[/tex]
Therefore the simplified form of given expression is [tex]x^2+4x-21[/tex].
The ages of the student in a dance class are 10 9 11 12 9 10 9 10 11 12 8 12 12. what is the mode for this set of data?
A corn vendor at a farmers market was selling a bag of 8 ears of corn for $2.56.Another vendor was selling a bag of 12 for $4.32.Which bag is the better deal?
To decide which one is the better deal, you need to compare them on price per ear. So, the the first vendor is $2.56/8ears= $0.32/ear
the second vendor: $4.32/12 = $0.36/ear
The first vendor with the bag of 8 ears is the better deal!
Answer:
The better deal is first vendor bag.
Step-by-step explanation:
Given : A corn vendor at a farmers market was selling a bag of 8 ears of corn for $2.56. Another vendor was selling a bag of 12 for $4.32.
To find : Which bag is the better deal?
Solution :
To compare which is better we find the unit rate of both vendor rate.
The selling price of first vendor of 8 ears of corn for $2.56.
The selling price of 1 bag is [tex]\frac{2.56}{8}[/tex]
The selling price of 1 bag is $0.32.
The selling price of second vendor of 12 ears of corn for $4.32.
The selling price of 1 bag is [tex]\frac{4.32}{12}[/tex]
The selling price of 1 bag is $0.36.
The unit price of first vendor bag is lower than second vendor.
So, the better deal is first vendor bag.
What is 23 as a fraction?
23%
23 / 100
if that is right your welcome